Den semiotiske tekstologi og fortolkningen af bibelske tekster - Petőfi, János Sándor (Religionsvidenskabeligt tidsskrift, 1993)
In the article the author presents the semiotic textology he has developed. In a demonstration of his model he discusses the Latin version of the Peter Noster, compared to some modern translations of it text in Matthew (6,7-). the article is a Danish translation of a paper given by the author at a conference on "Methodology in the Study of Religion", held at the University of Aarhus in June 1992.